UNITY: Building Bridges in a Hyperconnected World - Mokkhuntod, Jaruwan; Phuengpha , Noppawan (Procedia of Social Sciences and Humanities, 2024)
In today's interconnected global landscape, trust is the fundamental element that bridges communication gaps, ensures collaboration, and supports the successful operation of societies and economies. The rapid advancement of digital technology and the rise of hyperconnectivity allow individuals and organizations to interact without borders, yet these advancements also create new challenges for building and maintaining trust. This journal explores how trust can be fostered in a hyperconnected world, focusing on the "UNITY" framework, which stands for Unify, Networked Engagement, Integrity, Trustworthy Actions, and Yielding Positive Impact. This research adopts a qualitative approach to analyze how governments, businesses, and individuals can navigate the complexities of hyperconnectivity while promoting cooperation and transparency. Through a case study analysis and document review, the findings highlight how trust is built when there is a commitment to shared goals, ethical interactions, and collective responsibility. This paper argues that by embracing the UNITY principles, societies can mitigate the risks of misinformation, fragmentation, and instability in the digital age. The results of this study offer strategic recommendations for policymakers and institutions looking to enhance public trust in the era of hyperconnectivity, ensuring sustainable development, social cohesion, and economic growth.